Lichen planus with dysphagia: an interdisciplinary, monocentric study of quality of life and depression - Diehl, Rebecca; Decker, Annegrit; Schmitt-Graeff, Annette; Kreisel, Wolfgang; Schauer, Franziska (Frontiers in Medicine, 2025)
BackgroundLichen planus (LP) is an inflammatory condition affecting skin and mucous membranes. Esophageal LP (ELP) is an underrecognized form causing dysphagia, with significant potential impact on patient quality of life.ObjectiveTo comprehensively assess quality of life, health satisfaction, and psychological burden in LP patients with dysphagia, comparing outcomes between patients with confirmed ELP versus those with dysphagia attributed to oral LP (OLP) manifestations.MethodsProspective cohort study conducted at the University of Freiburg Medical Center including 47 patients with LP presenting with dysphagia. Following comprehensive dermatological assessment and esophagogastroduodenoscopy with biopsy, patients were categorized into ELP (n = 21, 45%) or non-ELP groups (n = 26, 55%). Patients completed validated questionnaires including the Dermatology Life Quality Index (DLQI), General Health Questionnaire-12 (GHQ-12), Patient Health Questionnaire-9 (PHQ-9), and comprehensive assessments of health satisfaction, quality of life, and symptom burden.ResultsNearly half of all patients (47%) expressed health dissatisfaction, with ELP patients showing significantly worse health satisfaction compared to non-ELP patients (p < 0.05). The psychological burden was substantial: 89% of patients exhibited pathological PHQ-9 scores indicating depression (42% moderate, 39% mild, 8% severe), while 55% screened positive for potential psychopathology on GHQ-12. Younger patients and women consistently reported higher disease burden across multiple measures. The mean DLQI was 7.56, with skin LP manifestations showing the highest impact (mean 9.61, p = 0.037). Notably, DLQI failed to capture ELP-specific burden, showing no significant difference between ELP and non-ELP groups.ConclusionLP patients with dysphagia experience profound quality of life impairment and psychological distress, with nearly 9 in 10 patients showing signs of depression. ELP patients demonstrate significantly worse health satisfaction than non-ELP patients, yet current quality of life instruments inadequately assess ELP-specific burden. The alarming prevalence of psychological comorbidities, particularly among younger patients, necessitates routine mental health screening and integrated psychological support in LP management. These findings provide critical evidence supporting comprehensive, interdisciplinary treatment approaches and justify advanced therapeutic interventions for this challenging patient population.